Nanotechnology and Development - Ramani, Shyama V. (Cambridge : Cambridge University Press, 2014)
This book identifies the nature and magnitude of the nanotechnology divide between high-income countries and the rest of the world.
Scientific publications
Keywords: Economic development -- Developing countries; High technology industries -- Developing countries; Nanostructured materials industry -- Developing countries; Nanotechnology -- Economic aspects